Disparities in Growth performance of Indian states: Empirical Evidence from Bihar and Kerala - Manish Kumar Singh (International Journal of Research in Social Sciences, 2018)
The disaggregated analysis of the regions of India is the curve of any discussion on economic development. The heterogeneity of Indian states gives importance to the special care needed in terms of regional development, keeping in mind that the high growth rate has not benefitted the states in the similar pattern. One way of study this is to examining disaggregated growth performance at the regional (state) level i.e., whether the growth performance is largely restricted to certain states of the country or not.Researcher has taken 36- year data of Per Capita Net State Domestic Product (PCNSDP) of Bihar and Kerala to identify inequality with in nation‘s growth performance.Semi-logarithmic regression model is employed for trend analysis and average annual percentage change for pattern analysis.Fluctuations in PCNSDP growth rate is more in Bihar as compared to Kerala. Kerala has experienced stagnantgrowth in PCNSDP since 1986-87 and after that, it has never turned back on declining path.While Bihar has experienced morevariation in course of growth.